Stent Thrombosis - Gopalakrishnan, Mukesh; Lotfi, Amir S. (Seminars in Thrombosis and Hemostasis, 2018)
The most dreaded complication with percutaneous coronary intervention with stents, either bare-metal or drug-eluting stents is stent thrombosis (ST) and it has a significant detrimental effect on the outcome for the patient. The initial attempts at intervention with bare-metal stents had much higher rates of ST compared with what is currently prevailing in the modern interventional world. Significant changes with respect to the stent technology, pharmacology, and most importantly our understanding of this phenomenon have decreased the risk of ST. There are many factors that can be performed to minimize the risk of ST and this review will describe the incidence, pathophysiology, and contributing risk factors to ST.
Keywords: stent thrombosis; bioresorbable vascular scaffolds; drug-eluting stents; bare-metal stents; dual antiplatelet therapy